2018
DOI: 10.1159/000494733
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-Term Outcomes in Elderly Patients with Hepatocellular Carcinoma after Curative Surgery: A Case-Controlled Study with Propensity Score Matching

Abstract: Background: With aging populations increasing in developed countries, the prevalence of elderly patients with hepatocellular carcinoma (HCC) is expected to rise. The aim of this study was to determine the short- and long-term outcomes of HCC surgery in elderly patients (≥75 years) using propensity score matching. Methods: The study group included 421 patients who underwent hepatectomy as their initial treatment with curative intent. The patients were divided into elderly (n = 111) and non-elderly (n = 310) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Several reports from the USA, UK, and Japan showed a significant age-specific increase in HCC development among persons over 70 years old [ 60 , 61 ]. From recent studies evaluating the clinical characteristics of elderly patients, it emerged that elders have less liver tissue fibrosis and fewer HCC nodules than younger patients [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports from the USA, UK, and Japan showed a significant age-specific increase in HCC development among persons over 70 years old [ 60 , 61 ]. From recent studies evaluating the clinical characteristics of elderly patients, it emerged that elders have less liver tissue fibrosis and fewer HCC nodules than younger patients [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that there are no substantial differences in complications among younger and elderly patients when the populations are correctly selected according to the guidelines [240][241][242][243][244][245][246][247][248][249], although some studies have reported a Grade 2 and 3 of complications according to the Clavien-Dindo classification [247,248].…”
Section: Surgical Therapymentioning
confidence: 99%
“…Therefore, older patients are more likely to have occlusive events, and their operative course needs closer attention than those of younger patients. Nonetheless, several reports have indicated that OLR for older patients with HCC is safe and feasible [ 12 14 ]. Conversely, the benefits of laparoscopic surgery for older patients with HCC remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have been conducted to evaluate the risk of surgical complications or the safety and efficacy of LLR for HCC in older patients [ 14 16 ]. Thus, this study aimed to examine the safety and feasibility of LLR for HCC in older patients using propensity score matching (PSM) analysis to reduce the effect of treatment or patient selection bias.…”
Section: Introductionmentioning
confidence: 99%